Colour and vitamin C equivalent antioxidant capacity of honey from different origins in Turkey - Bahar, Sinem; Korkmaz, Serol; Korkmaz, Burcu İrem Omurtag (ACTA Apicola Brasilica, 2022)
The nutritional content, antioxidant capacity and sensory characteristic such as colour vary related to botanical and geographical origins. The study was aim to investigate the spectrophotometric classification of honey colour by Pfund scale and the vitamin C equivalent antioxidant capacity (VCEAC) expressed as l-ascorbic acid equivalent by MTT assay. Eight honey samples originating from different geographical areas of Turkey were supplied and coded. The colour of the samples was determined as extra white (blossom-multifloral and citrus), white (blossom-multifloral and lavender), amber (thyme-Astragalus and honeydews) and dark amber (chestnut). The highest VCEAC was statistically measured in the honeydews and citrus honey, as the lowest was in the blossom and chestnut honey. And, there was no significant interaction between the colour score and the VCEAC of the honey. In conclusion, the honey from different botanical and geographical origins in Turkey showed the antioxidant capacity independently of their colour. The results needed further studies to investigate the floral diversity and phytochemical contents which influence the colour and antioxidant capacity of honey.